TAFSIR ALQURAN TRANSFORMATIF: Perspektif Hermeneutika Kritis Hassan Hanafi - Kurdi Fadal (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2014)
This research reveals Hassan Hanafi’s methodo- logical steps toward transformative interpretation, an interpre- tation that the starting point on the real experience of commu- nity. Hanafi takes two steps, namely the reading of the text of the Qur'an and reading community realities. Reading of the text adopted by specific approach (juz'i), thematic (maudu 'i), and refers to the text meaning (maqasid). While reading on the social context used: actual (Zamani), factual (waqi'i), and contextual, as well as recognize their realities. Hanafi assessed that this approach will bring the style of interpretation that really able to answer the problems of contemporary Muslim societies.